Mechanisms, strategies, and clinical application progress of subcutaneous transplantation angiogenesis - Li, Yiwen; Ye, Xuejin; Chen, Sheng; Guo, Lin; Xu, Zhiran; Chen, Jibing; Gao, Hongjun (Frontiers in Bioengineering and Biotechnology, 2025)
Subcutaneous transplantation, as an important technology in cell and tissue engineering, has received considerable attention due to its simplicity of operation, strong reproducibility, and potential clinical application value. However, the limitations of the vascular network in subcutaneous tissue severely restrict the survival and functionality of transplanted cells; therefore, angiogenesis has become a key factor in improving the success rate of transplants. Currently, despite progress in the research of subcutaneous transplantation, there are still many challenges and shortcomings. This article reviews the molecular mechanisms of angiogenesis in subcutaneous transplantation, strategies involving cells and biomaterials, as well as the latest technological advancements in promoting angiogenesis. It focuses on analyzing research results in aspects such as growth factor delivery, co-transplantation of cells, scaffold material optimization, and immune regulation. At the same time, the article systematically summarizes the clinical application prospects and challenges of subcutaneous angiogenesis strategies in islet transplantation, soft tissue repair, and autoimmune diseases. By comprehensively analyzing the current research hotspots and difficulties, it aims to provide theoretical support and practical guidance for future basic research and clinical translation of angiogenesis in subcutaneous transplantation.